An Exploratory Study Aimed at Understanding the Perceptions of Corruption in Political Leadership With Specific Reference to Sub-Saharan Africa - Hurburun, Kandayalal Sewraj (Auckland University of Technology, 2011)
The objective of this thesis is to investigate perceptions of political corruption in Africa, particularly the Sub-Saharan region. The various types of corruption are described and how these interlink is shown. This study also includes a review and utilization of various indices and measurements of corruption in an attempt to answer two fundamental questions namely: 1. Is the Sub-Saharan region of Africa more corrupt than other regions? 2. Are leaders in Sub-Saharan Africa as corrupt as perceived? The literature was reviewed with particular reference to definitions, types, causes and consequences of corruption. The review also identified some specific hypothesized causes and consequences of alleged corruption and perceptions of corrupt leadership in Sub-Saharan Africa. Furthermore, various published indices were identified through the literature review which can be accessed for the purposes of comparing the different levels of perceived political corruption relative to specific criteria such as; bribery, cronyism or “rent-seeking”. From the many indices available, five generally well known and documented indices and their respective datasets were selected for further analysis through this study. The sources of the selected indices for this study were from those provided by: Transparency International’s Corruption Perception Index; World Bank’s Country Rankings; ICRG (International Country Risk Guide’s) Failed State Index; Ibrahim Index’s Ranking and Good Governance; Afrobarometer’s Round 3 and Round 4 survey questions for 18 to 20 Sub-Saharan African countries respectively. In addition to some comprehensive datasets used in this study, other sources such as Freedom House’s Country Status ratings and the overview of other peripheral indices were also briefly referred to. The researcher collated the results of the major datasets and surveys contained in these indices and subsequently used two “data analysis tools” namely: SPSS and MS Excel to conduct the analyses mainly using simple correlations and other related statistical procedures. In terms of the combined quantitative and qualitative data, this study has shown that political corruption is prevalent in the Sub-Saharan region and that the allegations or perceptions for this appear to be credible. The extent and magnitude of political corruption is however, a critical question and will therefore require more investigation through further research. Despite the plausibility of corruption being prevalent for many countries within the Sub-Saharan region, this study has revealed that there are also a few other countries in the region which appear to be far more progressive than expected and may thus emerge as being less corrupt when compared to countries in other regions of the world. Selected corruption indicators such as “cronyism” and “nepotism” for example, when compared to non-OECD/non rich countries, indicated that some countries in the Sub–Saharan region were no more corrupt than other non-OECD/non-rich countries specifically in relation to these two selected indicators. With reference specifically to the Afrobarometer dataset used in this study, the analysis in this instance however, indicated that a few political leaders in Sub-Saharan Africa appeared to be as corrupt as perceived even though this dataset does not have full coverage of all of the Sub-Saharan African countries. It could thus be inferred from the literature and the various tests used in this study that in some instances, political leadership appears to be synonymous with perceived corruption in Sub-Saharan Africa. Moreover, “Political Leadership” as relevant to the Sub-Saharan region, is also often perceived as exploiting the spoils that come with this position which in turn alleges political corruption. Given that actual corruption is difficult to establish, the wide practice of patriarchal and tribal based traditional authority in the Sub-Saharan region further adds to the complexity of the perceptions of corruption. It is possible therefore that some arcane distinctions of what are a corrupt acts or what is entitlement may be conveniently blurred in contemporary political societies. Other facets of perceived corruption such as “bribery”, whilst considered by the writer to be one of the significant “indicators” of corruption for the region, appeared not to reveal any strong correlations across all tiers of government. These correlations for “bribery” however, were done using only the Afrobarometer survey data. Thus, the link in terms of the correlations between bribery and corruption for government in general within the context of the Afrobarometer survey data, has not been established. In a further analysis, one of the predictors for political corruption such as the levels of “GDP per capita” which was also expected to yield strong correlations between wealth in terms of GDP per capita and political corruption surprisingly did not reveal any significant relationships. GDP per capita was also negatively correlated with most of the other indices used in this study. Notwithstanding any significant correlations between low GDP and acts of bribery, the region still shows many areas of poor political leadership based on some of the causal symptoms of corruption. These symptoms may align themselves with alleged political corruption in varying degrees and are often manifested by many Sub-Saharan political leaders who display blatant arrogance and a total disregard for statesmanship through a lack of transparency and accountability. There are other manifestations that indicate a gross failure of political leadership and the subversion of good governance in this region of Africa. Indeed, there are the many political leaders including some of the ruling elite within the Sub-Saharan region who wilfully create political tension. To this end, thugs and loyal followers are actively recruited in further inciting others to commit savage acts of violence against innocent people including those who oppose the ruling party or leader. Such tensions eventually explode, giving rise to prolonged and on-going internal conflict. Under these conditions, malevolent leaders or incumbent leaders amongst the political elite who become complicit either directly or indirectly in wide scale political violence; who continue to persecute opposing factions to the point where there is a mass refugee efflux and; who deliberately encourage cross border wars thus creating wider tensions in the greater region. In a climate of heightened fear and where state resources are plundered to the point where innocent masses are left destitute and vulnerable, unscrupulous and indulgent political leaders become even more determined to stay in power. The Sub-Saharan region is replete both past and present with such types of political leadership who have boastfully and arrogantly extended their tenure within government. The trajectory of political corruption is seen not only through allegations of greed, financial mismanagement, embezzlement or other government malpractices but it is also visible when it takes hold of the entire state bureaucracy. To this end a complete subversion of all the principles of good governance becomes the status quo and thus “statecraft” itself is in essence, “corrupted”. This wilful dereliction of good governance by many political leaders in the Sub-Saharan region has already culminated in the total anarchy of Somalia, hence now regarded as a failed state. Aside from Somalia being a failed state, the Sub-Saharan region has also produced a number of other countries that have come very close to the precipice of total state failure, largely by the conduct of deluded and despotic leadership. In the writer’s assessment, the overall literature study undertaken, combined with the collective data analyses, suggests that political corruption amongst the rank and file of leadership including heads of states within many countries in this region is very likely. Given this scenario, some serious challenges lie ahead for some countries within the region.
Keywords: Sub-Saharan Africa; Africa; Corruption; Perceptions; Leadership; Political